2007
DOI: 10.1038/nrn2107
|View full text |Cite
|
Sign up to set email alerts
|

Agenesis of the corpus callosum: genetic, developmental and functional aspects of connectivity

Abstract: Agenesis of the corpus callosum (AgCC), a failure to develop the large bundle of fibres that connect the cerebral hemispheres, occurs in 1:4000 individuals. Genetics, animal models and detailed structural neuroimaging are now providing insights into the developmental and molecular bases of AgCC. Studies using neuropsychological, electroencephalogram and functional MRI approaches are examining the resulting impairments in emotional and social functioning, and have begun to explore the functional neuroanatomy un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
737
3
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 736 publications
(776 citation statements)
references
References 146 publications
(159 reference statements)
29
737
3
7
Order By: Relevance
“…ACC is among the characteristic features of ARX-associated lissencephaly. 26,27 The frequent association of ACC with vLIS-ND patients in our series suggests considering this feature as a supplementary criteria to differentiate cLIS from vLIS. It is important to note, however, that ACC may also be found in other types of lissencephalies.…”
Section: Resultsmentioning
confidence: 99%
“…ACC is among the characteristic features of ARX-associated lissencephaly. 26,27 The frequent association of ACC with vLIS-ND patients in our series suggests considering this feature as a supplementary criteria to differentiate cLIS from vLIS. It is important to note, however, that ACC may also be found in other types of lissencephalies.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with agenesis of the corpus callosum often have impoverished and superficial relationships, suffer from social isolation, and have interpersonal conflicts both at home and at work due to misinterpretation of social cues (Paul et al 2007). Kaufman et al (2008) found that the VENs were reduced by 50% in a subject with partial agenesis of the corpus callosum and 90% in a subject with complete agenesis, compared to adult controls.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of ECT in BTBR mice is particularly remarkable considering that these animals have profound and irreversible deficiency in interhemispheric connectivity due to the missing corpus callosum and underdeveloped hippocampal commissure [41,42], which is congruent with compromised long-range connectivity in autism [43][44][45]. However, it should be noted that the lack of corpus callosum alone cannot explain the presence of autism-like behavior; indeed, postnatal mechanical lesion to the corpus callosum in LP/J mice (which are genetically close to BTBR mice but show no autism-like behavioral abnormalities) failed to produce autism-like impairments [46].…”
Section: Discussionmentioning
confidence: 99%